Coping strategies for people living with HIV/AIDS in overcoming physiological, emotional, and psychosocial problems at the Victory Plus Yogyakarta - Zulaifah, Heni; Puspitawati, Theresia; Fitriani, Ayu (BKM Public Health and Community Medicine, 2021)
Background: Human Immune Deficiency Virus (HIV) is a potentially deadly virus that attacks the body's immune system. People with HIV/AIDS (PWHA) faced physiological disease, emotional problems such as depression, and psychosocial problems, such as stigma and discrimination. Preliminary studies revealed physiological problems as a side effect of antiretroviral virus (ARV), emotional problems such as stress and depression, and psychosocial issues of being stigmatized. Objective: This study aimed to explore deeply the coping strategies for physiological, emotional, and psychosocial problems of people living with HIV/AIDS (PLWHA). Method: This study was a qualitative study with a phenomenological research design. Researchers used a purposive sampling technique with a maximum variation sampling strategy collecting data through in-depth interviews and analyzing by content analysis. There were five subjects. Results: The five subjects experienced physiological problems as a side effect of using ARV and opportunistic infections. The coping strategies included problem-solving, utilizing social support, and looking for a silver lining. They treated themselves according to the symptoms. If they could not treat the disease by themselves, they visited the doctor for examination. However, if it was untreatable, they ignored it. For emotional problems, the informants used coping strategies that include problem-solving, utilizing social support, and looking for a silver lining; they encourage themselves and then ask their peers for help and instill positive thinking attitudes. However, some informants also vented negative issues, such as avoidance, self-blame, and wishful thinking. Some might suffer from drinking and blaming the self. The coping strategies for the psychosocial problems included compromise and looking for a silver lining; they used an approach to spend with friends and instill positive thinking in themselves. Conclusions: PLWHA used two-types strategies to cope with physiological, emotional, and psychosocial problems, namely positive coping strategies such as problem-solving, utilizing social support, looking for a silver lining, and compromise, and negative coping strategies such as self-avoidance, self-blame, and wishful thinking.